Extensive Metabolic Remodeling Differentiates Non-pathogenic and Pathogenic Growth Forms of the Dimorphic Pathogen Talaromyces marneffei - Pasricha, Shivani; MacRae, James I.; Chua, Hwa H.; Chambers, Jenny; Boyce, Kylie J.; McConville, Malcolm J.; Andrianopoulos, Alex (Frontiers in Cellular and Infection Microbiology, 2017)
Fungal infections are an increasing public health problem, particularly in immunocompromised individuals. While these pathogenic fungi show polyphyletic origins with closely related non-pathogenic species, many undergo morphological transitions to produce pathogenic cell types that are associated with increased virulence. However, the characteristics of these pathogenic cells that contribute to virulence are poorly defined. T. marneffei grows as a non-pathogenic hyphal form at 25°C but undergoes a dimorphic transition to a pathogenic yeast form at 37°C in vitro and following inhalation of asexual conidia by a host. Here we show that this transition is associated with major changes in central carbon metabolism, and that these changes are correlated with increased virulence of the yeast form. Comprehensive metabolite profiling and 13C-labelling studies showed that hyphal cells exhibited very active glycolytic metabolism and contain low levels of internal carbohydrate reserves. In contrast, yeast cells fully catabolized glucose in the mitochondrial TCA cycle, and store excess glucose in large intracellular pools of trehalose and mannitol. Inhibition of the yeast TCA cycle inhibited replication in culture and in host cells. Yeast, but not hyphae, were also able to use myo-inositol and amino acids as secondary carbon sources, which may support their survival in host macrophages. These analyses suggest that T. marneffei yeast cells exhibit a more efficient oxidative metabolism and are capable of utilizing a diverse range of carbon sources, which contributes to their virulence in animal tissues, highlighting the importance of dimorphic switching in pathogenic yeast.